The informal and underground economy of the South Texas border - Richardson, Chad, 1943- (Jack and Doris Smothers series in Texas history, life, and culture., 2012)
"Much has been debated about the presence of undocumented workers along the South Texas border, but these debates often overlook the more complete dimension: the region's longstanding, undocumented economies as a whole. Borderlands commerce that evades government scrutiny can be categorized into informal economies (the unreported exchange of legal goods and services) or underground economies (criminal economic activities that, obviously, occur without government oversight). Examining long-term study, observation, and participation in the border region, with the assistance of hundreds of locally embedded informants, The Informal and Underground Economy of the South Texas Border presents unique insights into the causes and ramifications of these economic channels. The third volume in UT-Pan American's Borderlife Project, this eye-opening investigation draws on vivid ethnographic interviews, bolstered by decades of supplemental data, to reveal a culture where divided loyalties, paired with a lack of access to protection under the law and other forms of state-sponsored recourse, have given rise to social spectra that often defy stereotypes. A cornerstone of the authors' findings is that these economic activities increase when citizens perceive the state's intervention as illegitimate, whether in the form of fees, taxes, or regulation. From living conditions in the impoverished colonias to President Felipe Calderón's futile attempts to eradicate police corruption in Mexico, this book is a riveting portrait of benefit versus risk in the wake of a "no-man's-land" legacy."--Publisher's website.